2013
DOI: 10.11118/actaun201260010091
|View full text |Cite
|
Sign up to set email alerts
|

Digestate is equal or a better alternative to mineral fertilization of kohlrabi

Abstract: In a one-year vegetation pot experiment, we compared the effect of digestate from a biogas station and mineral fertilisers on yield and quality parameters of kohlrabi, variety Segura F1. Four treatments were used in the trial: 1) untreated control, 2) urea, 3) digestate, 4) urea, triple super phosphate, KCl, MgSO4. The N dose was the same in treatments 2–4, 1.5 g N/pot. In treatment 4 the P, K and Mg doses corresponded to those supplied in the digestate treatment (3). The weight of single kohlrabi bulbs in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…The lowest nitrate content was observed in the unfertilised treatment and the second lowest nitrate content in the digestate treatment ( Table 8). The same results were described by Lošák et al [39] with kohlrabi variety Segura F1. The reason is probably that the digestate contains a significant proportion of organic N (25-50%), which is subject to mineralisation and subsequent nitrification only after a certain period [27].…”
Section: Content Of Ascorbic Acid and Nitrates In Bulbssupporting
confidence: 78%
See 1 more Smart Citation
“…The lowest nitrate content was observed in the unfertilised treatment and the second lowest nitrate content in the digestate treatment ( Table 8). The same results were described by Lošák et al [39] with kohlrabi variety Segura F1. The reason is probably that the digestate contains a significant proportion of organic N (25-50%), which is subject to mineralisation and subsequent nitrification only after a certain period [27].…”
Section: Content Of Ascorbic Acid and Nitrates In Bulbssupporting
confidence: 78%
“…However, no significant differences were found between these two treatments. Lošák et al [39] found the same yield results with kohlrabi of a different variety (Segura F1). In experiments lasting several years, Stinner et al [3] also reported positive effects of three different types of digestate (fermented clover-grass mixture, cover crops and post-harvest residues) on wheat yields.…”
Section: Weight Of Single Bulbssupporting
confidence: 63%
“…The residues generated during the production of biogas through anaerobic digestion of organic wastes are known as digestate that can represent a valuable resource to sustain and improve soil fertility and to increase soil organic matter content. It may be considered as an effective source of organic fertilizer as it contains considerable amounts of nutrients and organic matter [2,3]. Biogas technology is becoming popular in rural Bangladesh in view of escalating costs of fuels as well as soaring prices of chemical fertilizers which our farmers find difficult to buy for their sustainable crop production.…”
Section: Introductionmentioning
confidence: 99%
“…According to Rivard et al (1995) and Arthurson (2009) a low amount of plant available N in biogas residues (C:N org = 14:1; mineral N: total N = 0.5:1) is the result of the volatilization of considerable amounts of NH 3 during the digestion of the highly degradable organic C residues. In contradiction Lošák et al (2012) applying biogas residues with a C:N ratio of 4:1 to kohlrabi found a higher availability of the organic N, which had positive effects on yield formation. P uptake of ryegrass grown in the control medium was on the same level as of ryegrass grown in compost without and with additives, respectively (Figure 3).…”
Section: Resultsmentioning
confidence: 87%
“…Nevertheless negative effects, caused by N immobilization, mostly associated with yield decrease were also reported (Iglesias-Jimenez and Alvarez 1993). Besides, compost biogas residues are increasingly used as fertilizers because they contain plant nutrients like N, P, K and others, which favor yield formation of field crops (Bachmann et al 2011, Lošák et al 2012). …”
mentioning
confidence: 99%